Manjšalnice v slovanskih jezikih : oblika in vloga = Deminutivy v slavjanskih jazykah : forma i rolʹ = Diminutives in slavic languages : form and role (University of Maribor Press, 2015)
Diminutives in slavic languages : form and role. Minorities can be summed up very briefly: a formula word is added to the base word, and the creator is given a new meaning or becomes emotionally or otherwise marked. We only theoretically take the basics and add appropriate explanations to them according to their vocabulary, but in fact the experts study the already created works, and by considering their meanings and meaning nuances (in better dictionaries this is done with markers and also explanations), assessing the relationships between them, frequency and competitiveness types of works, semantic and other changes in time, in different languages ​​also landscape differences, which can be traced back to the past, and their variations in contact with other languages ​​and cultures, and etymology also joins the linguistic interest. When word-makers focus on minor characters as one of the results of word-forming processes, either in Slavic languages ​​or in Slovene as one of them, as in the present monograph, instructive, inviting and brilliant work is created for future research. A tale of exploratory devotion and passion, it encourages wonder and, with a multitude of examples, gives rise to new curiosity. What future Slovenian grammar will be able to more systematically capture minor phenomena that have not been the case before, and its authors will have the opportunity to eliminate the gaps in the common grammar consciousness. A great collection of little things that the authors have done mightily under the happy editorial arm.